Media frames and the sex offender: A qualitative content analysis from six major metropolitan areas - Navarro, John C. (Journal of crime and justice, 2023)
Media portrayals of sex offenders are often negative, suggesting that public attitudes share a one-dimensional portrait. But past scholarship has regularly relied on a single newspaper or combined national-regional newspapers when investigating the media framing of sex offenders, which has possibly masked the disparate discourse of sex crimes across geographies and outlets. Our qualitative content analysis of sex crime depictions in articles published between 2012–2016 from six daily newspaper outlets of major metropolitan areas demonstrates that the media framing of sex offenders is varied and multidimensional. Our analysis indicates four salient sex offender frames: the monstrous sex offender, the psychotic sex offender, the sex offender versus the victim, and the humanized sex offender. Each frame is constructed by distinctive scripts, or a sequence of events and actions to describe sex offenders and their offenses. As parts of the interpretative repertoire, sex offender frames and scripts are connected to specific policy initiatives from a conservative to a progressive orientation.